An Update on Recent Studies Focusing on the Antioxidant Properties of Salvia Species - Domenico Iacopetta; Jessica Ceramella; Domenica Scumaci; Alessia Catalano; Maria Stefania Sinicropi; Rosa Tundis; Stefano Alcaro; Fernanda Borges (MDPI AG, 2023)
Nutrition has crucial effects and a significant role in disease prevention. Recently, nutraceuticals have attracted much attention in scientific research due to their pleiotropic effects and relatively non-toxic behavior. Among the biological effects displayed by plants belonging to the Lamiaceae family, such as antibacterial, anticancer, anti-inflammatory, and anticholinesterase, sage is well known for its antioxidant properties and is a rich source of numerous compounds that are biologically active, amongst them polyphenols, with more than 160 types identified. In this review we summarized some of the significant studies published in the last decade reporting the most employed extraction methods and the different assays that are useful for establishing the antioxidant properties of some sage species. Even though the scientific literature contains plenty of data regarding the antioxidant properties of many sage species, further studies are needed in order to gain a deeper understanding of the mechanism of action and the compounds responsible for their antioxidant activity. Finally, it should be taken into account that the data on the antioxidant properties of sage extracts are often difficult to compare with each other, since a series of variables in the extraction procedures, the type of assay used, and standardization may affect the final result.